2012
DOI: 10.1007/978-94-007-4309-0_19
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Overview of Late Cretaceous Turtle Diversity in Eastern Central Europe (Austria, Hungary, and Romania)

Abstract: A preliminary overview of the relatively poorly known Late

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…These fossils, associated with typical marine taxa such as sharks and mosasaurs, were referred to possible terrestrial turtles and to theropod dinosaurs ( Averianov and Yarkov 2004a , 2004b ). Although the turtle remains were cited as resembling the basal turtle Kallokibotion ( Averianov and Yarkov 2004a ), these similarities were dismissed in a recent review of central-eastern European turtles by Rabi et al (2013a) . The poorly preserved theropod remains were referred to a dromaeosaurid (isolated tooth) or a more basal, non-avetheropod taxon (fragmentary braincase) ( Averianov and Yarkov 2004a ), although the heavily worn state of the latter specimen casts some doubts on this referral and it might belong to an indeterminate ankylosaur instead (Averianov, pers.…”
Section: The Late Cretaceous Continental Vertebrate Faunas Of Europementioning
confidence: 99%
“…These fossils, associated with typical marine taxa such as sharks and mosasaurs, were referred to possible terrestrial turtles and to theropod dinosaurs ( Averianov and Yarkov 2004a , 2004b ). Although the turtle remains were cited as resembling the basal turtle Kallokibotion ( Averianov and Yarkov 2004a ), these similarities were dismissed in a recent review of central-eastern European turtles by Rabi et al (2013a) . The poorly preserved theropod remains were referred to a dromaeosaurid (isolated tooth) or a more basal, non-avetheropod taxon (fragmentary braincase) ( Averianov and Yarkov 2004a ), although the heavily worn state of the latter specimen casts some doubts on this referral and it might belong to an indeterminate ankylosaur instead (Averianov, pers.…”
Section: The Late Cretaceous Continental Vertebrate Faunas Of Europementioning
confidence: 99%
“…The most frequent skeletal elements, beside those pertaining to dinosaurs, are Kallokibotion shell fragments, but, unfortunately, the precise ecological preferences (more aquatic or more terrestrial) of this primitive turtle remain poorly understood (Rabi et al, 2013).…”
mentioning
confidence: 99%
“…However, given that the "type publication" was placed in an abstract volume, the name is not considered published and is therefore unavailable for nomenclatural considerations (ICZN 1999). Rabi, Vremir et al (2013) already noted the problematic status of this taxon name, but incorrectly concluded that it represents a nomen invalidum (i.e., a junior synonym). Instead, this name should be considered a nomen nudum until finally made available for nomenclatural consideration under the rules of the ICZN (1999).…”
Section: Muehlbachia Nopcsai Vremir and Codrea 2009 Nomen Nudummentioning
confidence: 99%
“…The earliest record consists of fragments from the Barremian of Teruel Province, Spain (Murelaga Bereikua 1998), the SantonianVeszprém County, Hungary (Rabi, Vremir et al 2013), and the Aptian Castellón Province, Spain (Pérez-García et al 2014), all of which are herein considered to be undiagnostic of valid species. Considering that the early record is focused on Spain and that the Iberian Peninsula was closest to the southern continents during the Early Cretaceous (Stampfli and Hochard 2009), it is plausible that dortokids dispersed from Africa to Europe during the early Cretaceous via the Iberian Peninsula.…”
Section: Paleobiogeographymentioning
confidence: 99%
See 1 more Smart Citation